Genus Pterocarpus: A review of ethnopharmacology, phytochemistry, biological activities, and clinical evidence. (5th October 2021) - Аrbаin, Dаyаr; Saputri, Gita Ayu; Syahputra, Ghalib Syukrilah; Widiyastuti, Yuli; Susanti, Deny; Taher, Muhammad
Abstract: Ethnopharmacological relevance: The genus Pterocarpus (Fabaceae) has about 46 species that are distributed over Asia, especially Indonesia, Africa, and several countries in America. Particularly, P . indicus and P . santalinus have been recorded as ancestor recipe in the old Indonesian book ( Cabe puyang warisan nenek moyang ). These plants have found application in traditional medicine, such as in the treatment of inflammatory diseases, gonorrhoea, infection, coughs, mouth ulcers, boils, diarrhoea, as well as in the management of pain (as an analgesic). Aim of the review: The present review aimed to comprehensively summarise the current researches on the traditional and scientific applications of the genus Pterocarpus with regard to the phytochemical content, in vivo and in vitro bioactivities, as well as clinical evidence that may be useful for future drug development. Materials and methods: Information about the Pterocarpus genus were obtained from local classic herbal literature and electronic databases, such as PubMed, Scopus, and Google Scholar. The scientific name of the species and its synonyms were checked with the information of The Plant List. Additionally, clinical trial results were obtained from the Cochrane library. Results: Several phytochemical constituents of the plants, e.g., flavonoids, isoflavonoids, terpenoids, phenolic acids, and fatty acids have been reported. There are about 11 species of Pterocarpus that have been scientifically studied for their biological activities, including anti-inflammatory, anti-microbial, analgesic, and anti-hyperglycemic. Of which, the anti-hyperglycemic activity of the extracts and phytochemicals of P. indicus and P. marsupium is particularly remarkable, allowing them to be further studied under clinical trial. Conclusion: The present review has provided an insight into the traditional applications of the plants and some of them have been validated by scientific evidence, particularly their applications as anti-inflammatory and anti-microbial agents. In addition, the genus has demonstrated notable anti-diabetic activity in various clinical trials. Graphical abstract: Image 1